EFFECTIVENESS AND SAFETY OF NARROW BAND ULTRAVIOLET B THERAPY IN CHRONIC PLAQUE PSORIASIS - Paracha, Muhammad Majid; ., Irfanullah; Ali, Zafar; Amin, Said (Journal of Postgraduate Medical Institute, 2012)
Objectives: To determine the effectiveness and safety of narrowband ultraviolet B in chronic plaquePsoriasis. Methodology: This descriptive case series study was carried out at skin unit Lady Reading HospitalPeshawar from June 2009 to Dec 2010. Sixty patients suffering from chronic plaque psoriasis, between theages of 12 and 70 years were included in the study. Minimum erythema dose was determined in everypatient according to skin types (1-6). All the patients were exposed to narrowband ultraviolet B. At zero,fourth, eighth weeks and sixteen weeks, Psoriasis Area Severity Index (PASI) was determined and decisionwas made to increase or decrease the dose according to response of patient. Results: Out of sixty patients fifty eight patients showed response showing effectiveness of 97.1%. Twopatients showed poor response. Four patients suffered from moderate erythema itching and vesicles. Conclusion: Narrowband ultraviolet B is a safe and effective therapy for chronic plaque psoriasis but longterm follow up is needed to determine its carcinogenic effects.